MANAGEMENT OF MAJOR PRE AND POSTHARVEST FUNGAL DISEASE (ANTHRACNOSE) OF MANGO FRUITS – A REVIEW - MUSTAFA, G; IMRAN, M; NADEEM, S; AHMAD, M; IQBAL, A; ALI, I; HASNAIN, M; MANN, NA; HUSSAIN, R; AKRAM, M; HAMZA, MZ (Biological and Clinical Sciences Research Journal, 2024)
Mango Mangifera indica L having family Anacardiaceaeis an important fruit in Physical and Biological Sciences. It is a prominent tropical and subtropical fruit produced all over the world. It is a popular fruit in the national as well as an international market due to its exquisite flavor and high nutritional caloric value. However, mangoes are susceptible to a variety of illnesses at all phases of growth, from the plants in the nursery to the fruits in storage or transit. The mango tree, and especially the fruit, is home to a wide range of infections, including fungus, which may be important causes of fruit rot. Colletotrichum species cause anthracnose, a serious disease affecting various crop species, causing fruit blemishes and financial losses. Historically, physical treatments and synthetic fungicides were used, but research into sustainable protection strategies is needed to reduce hazardous chemicals. Pre-harvest and postharvest infections can impair fruit quality and result in significant losses. The visible exterior symptoms frequently appear after ripening, which is commonly associated with the edibility of the fruit and causes significant losses during storage. The economic consequences of such postharvest losses exceed the field losses. So far, chemical-based treatments have dominated mango disease control. However, because of growing worry over residual toxicity caused by the widespread use of synthetic fungicides and the emergence of resistance in pathogen populations, attention has shifted to nonchemical techniques. Biological agents and vegetal derivatives have shown effectiveness, but crucial problems must be resolved before they can be integrated into practical crop protection plans. Biotechnology-based strategies, including RNA interference and genome editing technologies, have shown potential for secure anthracnose control. However, despite their high specificity and potential side effects, several issues need to be addressed before they can be integrated into IPM procedures to prevent Colletotrichum spp. disease.